Time-Cost Relationship for Predicting Construction Duration - Czarnigowska, Agata; Sobotka, Anna (Budownictwo i Architektura / Civil and Architectural Engineering, 2013)
The paper aims at creating a model of road construction duration in the function of project qualities including the construction cost. The qualities considered are likely to be defined or possible to be estimated at early stages of project planning, giving no consideration to construction method or organisation of works. Potentially, the model might be applied by construction clients in their feasibility studies. It could also be used for comparing construction duration or construction rate with respect to project qualities.